Epigenetics and human reproduction - Rousseaux, Sophie; Khochbin, Saadi; SpringerLink (Online service). (Berlin Springer, 2011)
genetics is a rapidly expanding field in medical and biological research which concerns heritable traits that are not attributable to changes in the DNA sequence. Epigenetic mechanisms play key roles in many biological processes, and it has become clear that their disruption can gives rise to diverse pathologies in humans. Edited by preeminent experts, Sophie Rousseaux and Saadi Khochbin, this volume in the Epigenetics and Human Health series discusses the role of epigenetics in human reproduction. The book presents epigenetic transitions that are important at defined stages of gametogenesis and during meiosis. Several of the sixteen chapters written by experts in the field cover fundamental concepts discovered through cellular and biochemical work and from research on animal models. In other chapters, key examples are provided of how disruption of these mechanisms affects germ cell development and fertility, and contributes to the germinal cancers. Finally, the book discusses how in vitro manipulation and culture in assisted reproduction can epigenetically perturb germ cells, and how this can trigger disease phenotypes in the next generation. Conceived towards advanced students, medical professionals and research scientists, this is the first comprehensive textbook on this topic that will serve as a valuable reference during the years to come
Preface B. Jegou -- Part 1 - Medical aspects and questions raised on the molecular basis of epigenome involvement in reproduction -- Part 2 - Fundamental aspects of genome and epigenome reprogramming during gametogenesis -- Part 3 Re-organization of nuclear compartments during gametogenesis -- Part 4 - Fundamental aspects of gene expression regulation during gametogenesis -- Subject index.
Electronic reproduction.
Keywords: Reproduction -- Genetics; Human reproduction; Electronic books